Analysis of some heavy metals and estimation of pollution indexes in open solid waste disposal site: The case of Bahir Dar City, Bahir Dar, Ethiopia - Belay, Lijalem; Sheferaw Ayele, Hailu; Aklilu Solomon, Muluken (Ethiopian Journal of Science and Technology, 2025)
Urban areas with high population and expansions of industrial activities are subject to a vast generation of municipal solid waste (MSW). This study attempts to analyze heavy metals (Pb, Ni, Cd, and Cr) concentration in the soil of the open solid waste dumping sites of Bahir Dar city and estimate the pollution index. A 0.5 kg of 4 soil samples were collected from the MSW dumping site. The three samples were collected from three corners of an equilateral triangle of 30 m length of the open solid waste dumping site and one sample 50 m away from the dumping site for every 15 cm interval (5-20 cm, 20-35 cm, and 35-50 cm). The collected samples from each corner for the same depth were well mixed and digested by the wet digestion method and then subject to Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) for the determination of heavy metals. Finally, the concentrations of the heavy metals in the solid waste were compared with the reference soil to estimate the pollution indexes. The results of ICP-OES of heavy metals in the dumping site in mean concentrations of mg/kg were found: 465.37±27.5, 232.17±76.1, 46.27 ± 18.21, and 15.4 ± 14.09 for Cr, Pb, Ni, and Cd respectively. All the heavy metal concentrations were below the limit set by the Environmental Protection Authority of Victoria (EPA of Victoria) for the hazardous classification range for respective metals. The T-Test at p <0.05, showed a significant difference in the mean concentration of the metals (Pb and Cr) between the soil taken from the dumping site and the control site (reference soil). However, Ni and Cd did not show significant differences. So, Pb and Cr have a higher degree of dispersion to the nearby farmland than Ni and Cd. Finally, the PI (pollution index) value of Cr and Pb fall in slight pollution, whereas Ni and Cd fall in moderate and very severe pollution, respectively, and will pose a negative effect on the soil of the nearby farmland, plants, and the environment. Thus, the contamination of these bodies by heavy metals will become a risk to human health through food chain and groundwater resources contamination. So, the municipal city has to construct a proper incineration plant or landfill that considers the future population growth of the city.